Fungal Dysbiosis in Mucosa-associated Microbiota of Crohn’s Disease Patients - Liguori, Giuseppina; Lamas, Bruno; Richard, Mathias L.; Brandi, Giovanni; da Costa, Gregory; Hoffmann, Thomas W.; Di Simone, Massimo Pierluigi; Calabrese, Carlo; Poggioli, Gilberto; Langella, Philippe; Campieri, Massimo; Sokol, Harry (Journal of Crohn's and colitis, 2016)
Background and Aims: Gut microbiota is involved in many physiological functions and its imbalance is associated with several diseases, particularly with inflammatory bowel diseases. Mucosa-associated microbiota could have a key role in induction of host immunity and in inflammatory process. Although the role of fungi has been suggested in inflammatory disease pathogenesis, the fungal microbiota has not yet been deeply explored. Here we analysed the bacterial and fungal composition of the mucosa-associated microbiota of Crohn’s disease patients and healthy subjects. Methods: Our prospective, observational study evaluated bacterial and fungal composition of mucosa-associated microbiota of 23 Crohn’s disease patients [16 in flare, 7 in remission] and 10 healthy subjects, using 16S [MiSeq] and ITS2 [pyrosequencing] sequencing, respectively. Global fungal load was assessed by real time quantitative polymerase chain reaction. Results: Bacterial microbiota in Crohn’s disease patients was characterised by a restriction in biodiversity. with an increase of Proteobacteria and Fusobacteria. Global fungus load was significantly increased in Crohn’s disease flare compared with healthy subjects [p < 0.05]. In both groups, the colonic mucosa-associated fungal microbiota was dominated by Basidiomycota and Ascomycota phyla. Cystofilobasidiaceae family and Candida glabrata species were overrepresented in Crohn’s disease. Saccharomyces cerevisiae and Filobasidium uniguttulatum species were associated with non-inflamed mucosa, whereas Xylariales order was associated with inflamed mucosa. Conclusions: Our study confirms the alteration of the bacterial microbiota and is the first demonstration of the existence of an altered fungal microbiota in Crohn’s disease patients, suggesting that fungi may play a role in pathogenesis.